Use of botulinum toxin type a in temporomandibular disorder - HUAMANI,Mary Akemy Uehara (2017)
ABSTRACT Temporomandibular disorder (TMD) may be defined as a set of clinical scenarios involving the masticatory muscles, the temporomandibular joint (TMJ) and associated structures. Currently, 40 to 75% of the population has some sign of temporomandibular disorder, mainly pain located in the muscles of mastication in the pre-auricular region. The present clinical case was diagnosed as muscle temporomandibular disorder secondary to parafunction, as well as muscle hyperactivity due to surgical displacement of the left temporal muscle on two occasions, one for placement of aneurysm clips and the other for tumor excision from the supraorbital region on the left side. The patient sought medical and dental attention for 10 years due to constant headaches, tiredness and pain in the cheeks. The patient tried numerous bite-guards and pharmacological therapies to no avail. The American Academy of Orofacial Pain Questionnaire was applied combined with the Criteria for Research and Diagnostics (DRC) and a decision was made to use botulinum toxin type A in the masseter and temporalis muscles. An analog pain scale was applied over 90 days. Three days following the application of botulinum toxin type A, the patient reported a significant improvement with complete resolution of pain (level 0) after 90 days. At 12 weeks from starting treatment, facial muscle physiotherapy was introduced to strengthen the muscles of mastication and the patient remained pain-free, which allowed the preparation and adaptation of a snap-on prosthetic appliance. In conclusion, the use of botulinum toxin in patients with temporomandibular disorder should be considered as a viable therapeutic option.